The Effectiveness Of Nada's Career Counseling Model Towards Career Maturity And Self-concept Of Former Drug Addicts: A Qualitative Study - Amin Al Haadi Shafie; Hishamuddin Abdul Wahab; Siti Nubailah Mohd Yusof; Mohd Khairul Anuar Bin Rahimi; Nurhafizah Binti Mohd Sukor; Nurhafizah Binti Mohamad Yasin; Nurul Ashikin Binti Ahmat Miskam (HR Management Academic Research Society, 2024)
Volume: 9 No: 6 ( Page: 229 - 246)